2006
DOI: 10.1111/j.1468-2435.2006.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning the Language of a New Country: A Ten‐year Study of English Acquisition by South‐East Asian Refugees in Canada

Abstract: The University of Toronto Refugee Resettlement Project (RRP) investigated language acquisition over a ten-year period among a sample of 608 South-East Asian Refugees in Canada. Two years after arrival, 17 per cent spoke English well, 67 per cent had moderate command of the language, and 16 per cent spoke no English. Ten years later, 32 per cent had good language skills, 60 per cent moderate skills, and 8 per cent still spoke no English. The most rapid improvement occurred during the early years of resettlement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 39 publications
4
75
0
1
Order By: Relevance
“…In earlier studies on labor and family immigrants in Israel (Beenstock 1996;Beenstock, Chiswick and Repetto 2001), the United States (Gonzalez 2000), Norway (Hayfron 2001) and Belgium (Van Tubergen and Wierenga, forthcoming), a statistically significant, but small, positive effect of having followed a language course was found. In a study of South-East Asian refugees in Canada, however, no effect of participating in English language classes was found (Beiser and Hou 2000;Hou and Beiser 2006), but possibly the finding was the result of too little variation to demonstrate associations. I hypothesize that refugees who have completed an integration course in the Netherlands successfully, are more proficient in L2 than other refugees in the Netherlands.…”
Section: Extensions Of the Standard Empirical Modelmentioning
confidence: 75%
See 1 more Smart Citation
“…In earlier studies on labor and family immigrants in Israel (Beenstock 1996;Beenstock, Chiswick and Repetto 2001), the United States (Gonzalez 2000), Norway (Hayfron 2001) and Belgium (Van Tubergen and Wierenga, forthcoming), a statistically significant, but small, positive effect of having followed a language course was found. In a study of South-East Asian refugees in Canada, however, no effect of participating in English language classes was found (Beiser and Hou 2000;Hou and Beiser 2006), but possibly the finding was the result of too little variation to demonstrate associations. I hypothesize that refugees who have completed an integration course in the Netherlands successfully, are more proficient in L2 than other refugees in the Netherlands.…”
Section: Extensions Of the Standard Empirical Modelmentioning
confidence: 75%
“…In line with SEM, it was found that English skills were higher among men, among those who migrated to the United States at a young age, who resided in the United States for a longer time period and who obtained a college diploma (Fennelly and Palasz 2003). Another study examined language acquisition over a 10-year period for 608 Southeast Asian refugees who moved to Vancouver, Canada (Beiser and Hou 2000;Hou and Beiser 2006). Again, it was found that English skills were higher among men, among those who arrived at a younger age, those who had been in Canada for a longer time, and those who had obtained more pre-and post-migration education.…”
Section: Extensions Of the Standard Empirical Modelmentioning
confidence: 87%
“…Other youth develop proficiency in but lack fluency in the native language spoken at home (Delgado et al, 2005). Even when a youth is fluent in English, parents often are not (Alvarez, 1999;Fang & Wark, 1998;Hou & Beiser, 2006), thus presenting a challenge to obtaining parental consent for treatment of a child and subsequently engaging the parents in the child's treatment. Given the range of linguistic proficiency among refugee youth and their parents-and at times the preference for different language between child and parentservices need to be flexibly available in different languages.…”
Section: Language and Cultural Factorsmentioning
confidence: 98%
“…Rather, acquiring a language is "part of a broader process of social integration into the new society" (Mesch 2003: 42) and social inclusion in general (Morrice 2007). On a sociocultural level, language is an entry point into the new culture where performing the fundamental tasks of daily living becomes accessible (Hou and Beiser 2006). From a psychological perspective, linguistic ability helps create a sense of belonging and feeling that one is part of a larger community (UNHCR 2001).…”
Section: Language Acquisition and Competencementioning
confidence: 99%